Asymmetries in energy consumption: Efficiency of public spending across Portuguese municipalities - Ricardo de Moraes e Soares; Alexandre Morais Nunes; Pedro Pinheiro; Ana Catarina Kaizeler; Vanda Martins (Public and Municipal Finance)
The efficient allocation of public financial resources to energy consumption in Portuguese municipalities is one of the most discussed topics in public finance, given the growing relevance of sustainability and energy efficiency. The study analyzes how public spending affects energy efficiency through a combination of data analysis and hypotheses testing to assess the relationship between public spending and energy consumption. The methodology includes DEA analysis of the financial data and energy consumption of the municipalities, as well as the definition of hypotheses to determine the possible correlations between investment and efficiency. The results suggest that, in general, municipalities with higher levels of public spending have lower levels of energy efficiency. Meanwhile, municipalities with smaller budgets and fewer resources tend to be more efficient. The DEA analysis of the data suggests that energy efficiency is not directly related to the size and/or economic aptitude of municipalities but rather to their ability to adopt new technologies and more efficient budgetary and financial management practices. The hypotheses tested show varying levels of efficiency in public spending in relation to energy consumption. The study also concludes that public policies should focus on technological innovation and benchmarking to improve energy efficiency. The analysis suggests that collaboration between municipalities and the adoption of best practices are essential to tackle regional disparities and promote energy sustainability. AcknowledgmentsThis article is financed by Instituto Politécnico de Lisboa [Polytechnic Institute of Lisbon].